High Resolution Comparative Genomic Hybridization Detects 7–8 Megabasepair Deletion in PCR Amplified DNA(1) - Larsen, Jacob (Anal Cell Pathol, 2001)
We investigated if any change in spatial resolution of comparative genomic hybridization analysis could be detected when using DNA amplified by degenerate oligonucleotide primed PCR (DOP‐PCR) as opposed to the use of unamplified DNA. Five DNA samples from B‐cell leukemias with small 11q deletions were amplified by DOP‐PCR and analysed by means of high resolution comparative genomic hybridization (HR‐CGH) for the evaluation of aberration size detection limit. By means of HR‐CGH, we found the detection limit of DOP‐PCR CGH for deletions to be between 3 Mbp and 7–8 Mbp.